Pelatihan Konseling Kolaboratif untuk Konselor SMA - Ayi Najmul Hidayat (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
Counseling has a strategic role in facilitating the growth and development of counselees in schools. Counselee is able to develop the power of thinking and independence, as well as demanded upon making decisions, to continue to universities and working world. Counselors assume counselees are lack of ability to solve problems. Therefore, counselors need to implement collaborative counseling, so as to encourage the counselee to participate, utilize the capabilities, advantages and experiences of counselees. The method in this training, are: discussion, lecture, and demonstration/practice. The result of this training, can improve the spirit of counselors to understand and implement the concept of collaborative counseling and take part on the incoming trainings. The spirit of counselor would help in solving the problem of counselees and supporting educational success. This training can improve the ability of counselors in motivating the counselee to consult, and cooperate in solving matters. Counseling collaborative is relevant to the school conditions and very effective to solve the counselee’s problem.